Предмет: Алгебра,
автор: Guineu31
решить.
(4х-3)(-2х-8)=0.
Ответы
Автор ответа:
0
-8x²-32x+6x+24=0
-8x²-26x+24=0 | ÷2
-4x²-13x+12=0 | · ( - 1)
4x²+13x-12=0
D= b²-4ac = =13² - 4·4·(-12)= 169 + 192= 361
√D = √361 = 19
x1= -b+√D = -13+19 = 6 ( сократим на 2 ) = 3
2a 2·4 8 4
x2= -b-√D= -13-19= - 32 = -4
2a 2·4 8
Ответ: x1= 3 ; x2= - 4 .
4
-8x²-26x+24=0 | ÷2
-4x²-13x+12=0 | · ( - 1)
4x²+13x-12=0
D= b²-4ac = =13² - 4·4·(-12)= 169 + 192= 361
√D = √361 = 19
x1= -b+√D = -13+19 = 6 ( сократим на 2 ) = 3
2a 2·4 8 4
x2= -b-√D= -13-19= - 32 = -4
2a 2·4 8
Ответ: x1= 3 ; x2= - 4 .
4
Похожие вопросы
Предмет: Математика,
автор: chfhduff
Предмет: Математика,
автор: pozlonchik2309pozlon
Предмет: Математика,
автор: milleresenia2
Предмет: Математика,
автор: Аноним